Synthesis and Biological Activity of Some New Substituted 2-(aminoacyl) Aminobenzoxazoles and Dipeptide Derivatives - Gommaa, A.M.; El-Gazzar, M.A.; Latif, M.S.; Ahmed, F.S.; El-Cadi, F.E. (Asian Journal of Chemistry, 2010)
The synthesis of 2-(N-Pht-aminoacyl) aminobenzoxazoles (VI–IX) and 2-(N-Pht-aminoacyl) amino-5-chloro-(or 6-bromo- or 5-chloro-6-bromo-5-nitro-) benzoxazoles (X–XXV) has been achieved via the carbodiimide (DCC) method. Hydrazinolysis of the N-phthalyl derivatives (VI–XXV) affords the free aminoacyl derivatives (XXVI–XLV). Some Pht-dipeptide derivatives (XLVI–LV) has been synthesized using the DCC method. Many of the prepared compounds were found to be active against a number of microorganisms.